Retrospective analysis of neurofilament-light chain in patients with inflammatory bowel disease – A pilot study - Andreas Wolff; Emily Feneberg; Julius Shakhtour; Katja Steiger; Roland M. Schmid; Bernhard Haller; Nya Reinhardt; Moritz Middelhoff; David Schult-Hannemann; Paul Lingor (PLoS ONE, 2026)
Background Chronic inflammatory bowel diseases, encompassing Crohn’s disease and ulcerative colitis, are characterized by persistent inflammation of the gastrointestinal tract. While traditionally regarded as confined to the gut, the systemic nature of inflammatory bowel disease has been increasingly recognized. The nervous system has garnered particular attention due to molecular and clinical evidence suggesting a potential interplay between inflammatory bowel disease and neurodegenerative diseases. Inflammatory bowel disease patients have a higher risk of developing neurological disorders such as Parkinson’s disease, all-cause dementia, and multiple sclerosis. Still, causative molecular mechanisms are poorly understood. Neurofilament light chain (NfL) has been established as a disease-independent biomarker of axonal damage reflecting neurodegeneration. Methods In this pilot study, we assessed molecular evidence of neurodegeneration by measuring serum NfL in a single-molecule array using the HD-X SIMOA platform (Quanterix, MA, USA) and employing correlation with clinical data in forty-nine patients with histopathologically confirmed inflammatory bowel disease. In total, 24 Crohn’s disease patients, 25 ulcerative colitis patients, and 23 controls, aged 18–79 years, were included. Results We found an age-dependency of serological NfL levels, however, no apparent differences between disease groups and controls. Crohn’s disease patients showed a slower age-dependent incline in serological NfL compared to control subjects (p = 0.03). No correlation of NfL with disease duration, disease severity, or inflammatory bowel disease treatment was found. Conclusions A slower age-dependent increase in serological NfL levels was found in Crohn’s disease patients compared to control subjects. Larger studies assessing additional markers of neurodegeneration may be instrumental in addressing this question in the future.